Clinical Significance of Expression of Topoisomerase 2а in Breast Cancer - A. A. Samuseva; R. V. Lyubota; A. S. Zotov; R. I. Vereshchako (Антибиотики и Химиотерапия, 2020)
Topoisomerases are enzymes that control the topology of DNA. Topoisomerases are divided into types 1 and 2, depending on the mechanism of action. The article discusses the structure and mechanisms of the action of topoisomerases, the possibility of an independent value of the level of expression of topoisomerase 2a in the course of chemotherapy with anthracycline antibiotics that inhibit this protein in patients with breast cancer.